Promosi Judi Online melalui Media Sosial: Studi tentang Penegakan Hukum dan Hukum Pidana Islam - Nur Amelia; Yuswalina Yuswalina; Jon Heri (CV. Doki Course and Training, 2025)
The development of technology and the internet brings convenience but also has negative impacts, one of which is the promotion of online gambling through Instagram. The phenomenon of influencers promoting online gambling through social media Instagram, which has negative effects on the social order, is becoming increasingly prevalent. Thus, to determine whether the penalties stipulated by the ITE Law are relevant to Islamic Criminal Law, it is necessary to conduct research on how the crime of promoting online gambling on Instagram according to Law Number 1 of 2024 on Information and Electronic Transactions, and how Islamic Criminal Law views the criminal sanctions for those promoting online gambling on Instagram. The approach method used in this research is the normative juridical method. This research is qualitative and includes library research data, largely drawn from published reference books. Among the primary legal materials are the Qur'an, Hadith, the ITE Law, and the Criminal Code. The research concludes that the act of promoting online gambling on the Instagram social media platform, according to Law Number 1 of 2024, can be seen from the actions taken in promoting online gambling, including distributing, transmitting, and/or electronic documents containing gambling content. The criminal sanctions against those promoting online gambling are imposed under Article 45, Paragraph 3 of Law Number 1 of 2024 on Information and Electronic Transactions, which stipulates a maximum prison sentence of 10 (ten) years and/or a fine of up to Rp.10,000,000,000.00 (ten billion rupiah). In Islamic Criminal Law, the crime of promoting online gambling has not been clearly regulated in the texts of the Quran or Hadith, so this crime is determined with ta’zir punishment.